Windows of Opportunity: Temporal Patterns of Technological Adaptation in Organizations - Tyre, Marcie J.; Orlikowski, Wanda J. (Organization Science, 1994)
This paper examines the introduction and adaptation of technologies that support productive operations. The authors argue that the process of technological adaptation is not gradual and continuous, as often argued in the innovation literature, but is instead highly discontinuous. Evidence from three manufacturing and service organizations indicates that there exists a relatively brief window of opportunity to explore and modify new process technology following initial implementation. Afterwards, modification of new process technologies by users is limited by the increasing routinization that occurs with experience. Thus, the technology and its context of use tend to congeal, often embedding unresolved problems into organizational practice. Subsequent changes appear to occur in an episodic manner, triggered either by discrepant events or by new discoveries on the part of users. These findings have important implications for theories of technological change.